Medium Range Order in High Aluminum Content Amorphous Alloys Measured by Fluctuation Electron Microscopy - Stratton, William (My University, 2007)
High Al-content metallic amorphous alloys have an unusual devitrification behavior. Upon annealing, alloys made by a rapid quench develop a high density (>1021 m-3) of pure Al nanocrystals. These alloys show a steadily decreasing heat flow signal in isothermal calorimetry and a steadily decreasing nucleation rate, suggesting heterogeneous nucleation. This data implies that a high density of nanoscale structural precursor sites is needed to account for the large number of nucleation events. One possible form of the precursor site in high Al-content amorphous alloys, and other amorphous materials, is atomic structure at the nanoscale (typically 1-3 nm), which is called medium-range order (MRO). This is to distinguish it from short-range order, typically first- and second-nearest neighbor atomic distances, and long-range order, typical of atomic spacing in crystals. MRO can be described as non-trivial three- or four-atom correlations or (in some cases) as small pockets of structural order in an otherwise disordered matrix. Fluctuation electron microscopy (FEM) is a quantitative electron microscopy technique that uses spatial fluctuations in diffraction from nanoscale volumes using the image variance to detect MRO in amorphous materials. To aid in interpretation of FEM results, we developed a new phenomenological theory which uses the assumed structure of a nanocrystal / amorphous composite for various amorphous materials to explicitly calculate the image variance as a function of experimental parameters. This model therefore connects the FEM signal to well-defined aspects of the material?s structure, enabling us to make statements on how a different FEM results relate to changes in the sample structure of high Al content amorphous alloys. FEM on multiple high Al-content metallic amorphous alloys (Al92Sm8, Al88Y7Fe5, and Al88Y7Fe4Cu1) found Al-like MRO present in the as quenched state of these materials. Experiments on the deformation induced alloy Al92Sm8 found a different type of MRO, which implies that the Al-like MRO in the as quenched material is associated with the devitrification reaction of high Al-content amorphous alloys. Using our FEM theory, we determined that the crystal Al-like volume fraction increases 60% when Al88Y7Fe5 is alloyed with Cu. This is correlated with a measured increase in the crystal volume fraction in Al88Y7Fe5 and Al88Y7Fe4Cu1 upon devitrification. Taken together, this work supports the quenched-in nuclei hypothesis for high Al-content amorphous alloy devitrification. In this picture, small proto-crystals are frozen into the material during the rapid quench process and later act as nucleation sites for the high density of Al nanocrystals that form upon devitrification. It is these proto-crystals that we measure with FEM. This is a crystal growth mechanism rather than a grain coarsening mechanism. As seen by the FEM results, these proto-crystals can be modified by alloying or processing to tailor the macroscale properties of the material.
Keywords: medium range order; metallic glass; fluctuation electron microscopy